STRENGTHENING FAMILY RESILIENCE THROUGH COLLABORATIVE GOVERNANCE IN WOMEN AND CHILD PROTECTION SERVICES AT DP3APPKB OF SURABAYA CITY - Karlina Winaryanti; Ulul Albab; Ika Devi Pramudiana (International Journal of Multidisciplinary Reseach, 2026)
This study aims to analyze the strengthening of family resilience through collaborative governance in women and child protection services at the Dinas Pemberdayaan Perempuan, Perlindungan Anak, dan Pengendalian Penduduk dan Keluarga Berencana Kota Surabaya. The research is motivated by the increasing complexity of urban social problems that contribute to the vulnerability of women and children and weaken family resilience. A qualitative approach with a case study design was employed. Data were collected through in-depth interviews, observation, and document analysis. The data were analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings Indicate that collaborative governance has been implemented through cross-sectoral coordination involving law enforcement agencies, healthcare providers, social workers, psychologists, and civil society organizations. This practice aligns with the collaborative governance framework proposed by Ansell and Gash, emphasizing dialogue, trust-building, and shared commitment among stakeholders. The integrated service model contributes positively to victims’ recovery and enhances family resilience, particularly in terms of emotional support, social stability, and adaptive capacity after crises. However, the study also reveals that collaborative governance has not been fully institutionalized, particularly regarding data integration systems and standardized operational procedures. Strengthening institutional frameworks, digitalizing service systems, and enhancing human resource capacity are necessary to ensure sustainable and accountable public service delivery. This research contributes theoretically to the development of collaborative public administration and offers practical recommendations for local governments in promoting inclusive and resilience-oriented protection services for women and children.